3-D High-Resolution Imaging Algorithm Using 1-D MIMO Array for Autonomous Driving Application - Yuan, Sen; Fioranelli, Francesco; Yarovoy, Alexander G. (IEEE transactions on radar systems, 2024)
The problem of 3-D high-resolution imaging in automotive multiple-input multiple-output (MIMO) side-looking radar using a 1-D array is considered. The concept of motion-enhanced snapshots is introduced to generate larger apertures in the azimuth dimension. For the first time, 3-D imaging capabilities can be achieved with high angular resolution using a 1-D MIMO antenna array, which can alleviate the requirement for large radar systems in autonomous vehicles. The robustness to variations in the vehicle's movement trajectory is also considered and addressed with relevant compensations in the steering vector. The available degrees of freedom, as well as the signal-to-noise ratio (SNR), are shown to increase with the proposed method compared to conventional imaging approaches. The performance of the algorithm has been studied in simulations, and validated with experimental data collected in a realistic driving scenario.